Malaria: Epidemiologi dan Diagnosis - Lukman Hakim (Loka Litbang Kesehatan Pangandaran, 2011)
Abstract. Malaria is an infectious disease caused by Plasmodium spp, are naturally transmittedby the mosquito Anopheles spp. Malaria transmission occurs because of interactionbetween the agent, the definitive host and intermediate hosts (humans). Therefore, the transmissionof malaria is influenced by the presence and fluctuations in vector populations (i.etransmitting mosquito Anopheles spp).Malaria diagnosis consists of clinical diagnosis and diagnosis based on laboratory examination.Clinical diagnosis or clinical malaria diagnosis was presumptive diagnosis of malariabased on clinical examination of patients with symptoms include fever (periodical), heat,level of consciousness, dizziness, etc. as well as specific local typical symptoms. Experiencesof medical personnel who perform precise diagnosis will determine whether or not the diagnosis,so that clinical diagnosis cannot be the main reference in the treatment of malaria becauseof high error rates.